An evaluation of the informative usefulness of the land administration system for the Agricultural Land Sales Control System in Poland. Issue 3 (1st September 2020) - Klimach, Anna; Dawidowicz, Agnieszka; Dudzińska, Małogrzata; Źróbek, Ryszard
ABSTRACT: Agricultural land is a limited resource. Poland has implemented new legal regulations to protect the sale of agricultural land. An Agricultural Land Sales Control System (ALSCS) has been called into existence for the purpose of real estate marketing. The currently implemented National Land Administration System, referred to as the Integrated Real Estate Information System (IREIS), was analysed to determine the extent to which it supports farmland management policies. The results of the study indicate that the IREIS is a fit-for-purpose ALSCS which offers a high degree of protection for agricultural land. The IREIS can effectively protect agricultural land during market transactions.